2004
DOI: 10.1038/nature02714
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen sensation and social feeding mediated by a C. elegans guanylate cyclase homologue

Abstract: Specialized oxygen-sensing cells in the nervous system generate rapid behavioural responses to oxygen. We show here that the nematode Caenorhabditis elegans exhibits a strong behavioural preference for 5-12% oxygen, avoiding higher and lower oxygen levels. 3',5'-cyclic guanosine monophosphate (cGMP) is a common second messenger in sensory transduction and is implicated in oxygen sensation. Avoidance of high oxygen levels by C. elegans requires the sensory cGMP-gated channel tax-2/tax-4 and a specific soluble g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
725
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(741 citation statements)
references
References 32 publications
11
725
1
4
Order By: Relevance
“…elegans reacts to a wide variety of chemical (for example, odorants, tastants and oxygen, etc.) and mechanical (for example, body and nose touch) stimuli and is commonly used as a model for the study of sensory transduction [23][24][25][26][27][28] . In this study, we found that phototaxis behavior is present in C. elegans, a soil-dwelling organism that lacks specialized light-sensing organs.…”
Section: Discussionmentioning
confidence: 99%
“…elegans reacts to a wide variety of chemical (for example, odorants, tastants and oxygen, etc.) and mechanical (for example, body and nose touch) stimuli and is commonly used as a model for the study of sensory transduction [23][24][25][26][27][28] . In this study, we found that phototaxis behavior is present in C. elegans, a soil-dwelling organism that lacks specialized light-sensing organs.…”
Section: Discussionmentioning
confidence: 99%
“…These have now been described, albeit to a limited degree, and include the "mammalian target of rapamycin" (mTOR) energy sensing 94 , the "unfolded protein response" (UPR) 95, and soluble guanylate cyclase 96 pathways. O 2 sensation by the developing nervous system, while poorly understood, also ultimately impacts behavioural responses in adult animals 96 . In C. elegans this involves neural cGMP-gated channels and a soluble guanylate cyclase homologue, GCY-35 that directly binds O 2 via a haem domain.…”
Section: Additional Mechanisms Regulating Embryogenesismentioning
confidence: 99%
“…elegans strains collected from all over the world show inheritable foraging differences that are only partially due to the naturally variable neuropeptide receptor npr-1, located on chromosome X. NPR-1 can occur in two isoforms: NPR-1 215V, with valine at position 215 and the less potent isoform NPR-1 215F, with phenylalanine at position 215 (24). NPR-1 modulates the O 2 sensing neurons AQR, PQR, and URX, which mediate avoidance of high O 2 and O 2 /CO 2 concentrations (21-11%) (17,(25)(26)(27). Not the variability in the NPR-1 receptor is responsible for the difference in foraging behavior between C. elegans strains, also the recently discovered globin, GLB-5, plays a role (15,17).…”
Section: Glb-5mentioning
confidence: 99%
“…This slowing down in response to slightly lower O 2 concentrations was weaker when food was absent, suggesting that this behavior is part of a foraging strategy. C. elegans strains containing the glb-5 (Bri) allele in combination with npr-1 215V moved slowly when feeding in all three mentioned O 2 concentrations (21, 19.2, and 17.4%) (15,17,(27)(28)(29). GLB-5 modulates the same O 2 sensing neurons as NPR-1 (AQR, PQR, and URX), which also express GCY-35 and GCY-36, subunits of soluble guanylate cyclases that also act as oxygen sensors (25,(30)(31)(32)(33).…”
Section: Glb-5mentioning
confidence: 99%